Suitability of Multinutrient Extractant for Estimating Micronutrients Cations in Different Soil Orders of Punjab, India - Vivek Sharma; Janpriya Kaur; S.S. Dhaliwal; Vicky Singh; Manmeet Kaur; Prabhjot Singh; S.K. Behera (Journal of the Indian Society of Soil Science, 2026)
Successful and sustainable crop production depends upon balanced nutrition of the crops. The soil testing provides an index of the available nutrients in soils and evaluation of multi-nutrient extractants is essential. Therefore, the present study was planned to evaluate the suitability of different extractants i.e. Ammonium bicarbonate-diethylene triamine pentaacetic acid (AB-DTPA), Mehlich 3 (M-3), Mehlich 1 (M-1) and Haney Haney Hossner Arnold (H3A) with standard Diethylene triamine pentaacetic acid (DTPA) extractant for determination of available micronutrients in 3 soil orders viz. Alfisol, Inceptisol and Aridisol of Punjab. The outcomes of experiment indicated the M-3 followed by AB-DTPA were most suitable and efficient for extraction of micronutrients in all soil orders of Punjab. However, for soil orders the declining trend of micronutrient distribution was Inceptisol>Alfisol>Aridisol. The correlation and regression studies indicated the highest positive and significant relation of DTPA with M-3 extractant. Therefore, it can be concluded the M-3 and DTPA extractant are most suitable and efficient for extraction of all micronutrients cation (zinc, iron, manganese, copper) from different soil orders of Punjab.